Ser-127-to-Leu substitution in the DNA gyrase B subunit of Streptococcus pneumoniae is implicated in novobiocin resistance. - Muñoz, R (1995)
We report the cloning of the gyrB gene from Streptococcus pneumoniae 533 that carries the nov-1 allele. The gyrB gene codes for a protein homologous to the gyrase B subunit of archaebacteria and eubacteria. The same amino acid substitution (Ser-127 to Leu) confers novobiocin resistance on four isolates of S. pneumoniae. This amino acid position is equivalent to Val-120 of Escherichia coli GyrB, a residue that lies inside the ATP-binding domain as revealed by the crystal structure of the protein.